Oxygen Reduction on Methanol-Tolerant Carbon-Supported PtxSy Nanoparticles Prepared by a Single-Step Low-Temperature Method - Carbonio, Emilia A.; Rodrigues-Filho, Ubirajara P.; Mesquita, Alexandre [UNESP]; Landers, Richard; Gonzalez, Ernesto R. (Springer, 2019)
In direct methanol fuel cells (DMFCs), the methanol crossover from the anode to the cathode is a major cause of power density loss because of the overpotential arising due to the parasitic reaction of methanol oxidation at the cathode. Catalysts modified with S have shown better methanol tolerance; however, the preparation routes often require high temperatures or pressures and very long times, making these expensive and unlikely to be used in large scale. Here, we report on a single-step low-temperature method used to prepare a carbon-supported PtxSy catalyst. Moreover, we show that the catalyst shows lower depolarization in the presence of methanol and study the effect of reductive thermal treatment and electrochemical potential cycling.
Keywords: Oxygen reduction reaction; Methanol tolerance; DMFC; PtxSy nanoparticles